ENVIRONMENTAL ASSESSMENT OF SOIL FOR EXAMPLE BRYANKA TERRITORIAL-INDUSTRIAL AGGLOMERATION (LUHANSK REGION) - Kononov, Y.; Udalov, I.; Chomko, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The complex of problems encountered in the restructuring of the coal mines Bryanka region Lugansk region. Describes the spread of certain trace elements in industrial waste Donbass. Point out possible sources of their income.